(untitled) (INTEGRATION PROCEEDING, 2023)
Hypertension is a chronic disease that is a health problem throughout the world. According to the World HealthOrganization (WHO), nearly 1.8 billion people each year die from hypertension in the Asian region. Hypertensivepatients need self-care to improve their health status. One component that affects self-care of hypertensive patients is self-efficacy. Patients who have high self-efficacy have 11 times the opportunity to show good medication adherence compared to patients who have low self-efficacy. This study is to determine the relationship between self-efficacy and adherence to taking antihypertensive drugs at UPT. Cempaka Health Center, Banjarmasin City. Research with crosssectional. The sample is people who seek treatment at UPT. Cempaka Public Health Center Banjarmasin City and diagnosed with level 2 hypertension patients amounted to 43 people. data collection technique is purposive sampling. Using a questionnaire as a measuring tool. Data were analyzed by Sperm rho test. Self-efficacyof people suffering from level 2 hypertension in the UPT area. Cempaka Public Health Center Banjarmasin City is included in the category of self-efficacy of 69.8%, compliance is 60.5% and there is a significant relationship between self-efficacy and drinking compliance with a significant value of p value = 0.001, the correlation coefficient is 0.503 which is included in the medium category and the direction of the correlation is positive. (+) which means unidirectional. There is a significant relationship between self-efficacy and adherence to taking antihypertensive drugs at UPT. Cempaka Health Center, Banjarmasin City.